Pengaruh Good Corporate Governance dan Pengungkapan Sustainability Report terhadap Kinerja Keuangan Perusahaan - Zuraida Innasya; Widiatmoko, Jacobus; Indiarti, Maria (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
The aim of this research is to determine the effect of good corporate governance and sustainability report disclosure on financial performance with company size as a control variable in basic industrial and chemical companies listed on the Indonesia Stock Exchange (BEI) for the 2018-2022 period. Aspects of good corporate governance are proxied by institutional ownership, independent board of commissioners and audit committee. Financial performance in this research uses the profitability ratio, namely Return On Assets (ROA). Sample selection was carried out using a purposive sampling method, the result was that 53 companies became research objects. Data analysis was carried out using multiple linear regression techniques, run through the IBM SPSS Statistics 26 program. The findings from this study indicate that sustainability report disclosures have a significant positive influence on financial performance. However, factors such as institutional ownership, the existence of an independent board of commissioners and the structure of the audit committee apparently do not have a significant impact on the company's financial performance.